Landman. Season one [videorecording (DVD)] - Sheridan, Taylor (Paramount, 2025)
Set in the proverbial boomtowns of West Texas, Landman is a modern-day tale of fortune seeking in the world of oil rigs. The series is an upstairs/downstairs story of roughnecks and wildcat billionaires fueling a boom so big, it's reshaping our climate, our economy and our geopolitics. --